Competitive Failure of Loosening and Fatigue of Bolts under Composite Excitation - Guang-Wu Yang; Long Yang; Shou-Ne Xiao; Shi-Lin Jiang; Wei Ma (Shock and Vibration)
At present, research on the loosening of bolts under transverse excitation and their fatigue under axial excitation has been relatively mature, but research on the competitive relationship and failure characteristics between loosening and fatigue of bolts under transverse and axial composite excitation is still insufficient. Therefore, a method to accurately determine the failure types of bolts is proposed in this study by conducting a competitive failure test of loosening and fatigue under composite excitation. According to this method, the failure types of bolts can be distinguished. The analysis results reveal that there is an obvious competitive failure relationship between the loosening and fatigue of bolts, and the failure mode is mainly affected by the ratio of the transverse and axial loads (ξ). There is a critical ξ of bolt-loosening or fatigue failure, and the critical ξ is an inherent property of the bolt and is unrelated to the load. The critical ξ of 8.8 grade M8 × 1.25 × 70 high-strength bolts under composite excitation is obtained as 0.075 mm/kN. The failure mode of bolts under composite excitation can be predicted based on the critical ξ.